2021
DOI: 10.1126/sciadv.abe1127
|View full text |Cite
|
Sign up to set email alerts
|

Controlled levitation of nanostructured thin films for sun-powered near-space flight

Abstract: We report light-driven levitation of macroscopic polymer films with nanostructured surface as candidates for long-duration near-space flight. We levitated centimeter-scale disks made of commercial 0.5-micron-thick mylar film coated with carbon nanotubes on one side. When illuminated with light intensity comparable to natural sunlight, the polymer disk heats up and interacts with incident gas molecules differently on the top and bottom sides, producing a net recoil force. We observed the levitation of 6-mm-diam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…With the existence of a temperature difference (Δ T ) at the object surface, the gas molecules around the high-temperature side will exert a larger force on the object than the low-temperature side, resulting in a net force toward the low-temperature side ( Shvedov et al., 2010 ). Alternatively, when one side of the object has a larger thermal accommodation coefficient than the other side, the gas molecules will leave the surface with a higher average velocity after the collision, leading to the net momentum transfer and a photophoretic force pointing to the side with a lower thermal accommodation coefficient ( Azadi et al., 2021 ). Photophoresis has been widely exploited for the manipulation of light-absorbing objects, such as carbon spheres ( Porfirev, 2019 ; Shvedov et al., 2009 ), carbon nanotube clusters ( Pan et al., 2012 ; Wang et al., 2016 ), and absorbing plates ( Cortes et al., 2020 ).…”
Section: Optical Techniques For Manipulation On Solid Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the existence of a temperature difference (Δ T ) at the object surface, the gas molecules around the high-temperature side will exert a larger force on the object than the low-temperature side, resulting in a net force toward the low-temperature side ( Shvedov et al., 2010 ). Alternatively, when one side of the object has a larger thermal accommodation coefficient than the other side, the gas molecules will leave the surface with a higher average velocity after the collision, leading to the net momentum transfer and a photophoretic force pointing to the side with a lower thermal accommodation coefficient ( Azadi et al., 2021 ). Photophoresis has been widely exploited for the manipulation of light-absorbing objects, such as carbon spheres ( Porfirev, 2019 ; Shvedov et al., 2009 ), carbon nanotube clusters ( Pan et al., 2012 ; Wang et al., 2016 ), and absorbing plates ( Cortes et al., 2020 ).…”
Section: Optical Techniques For Manipulation On Solid Substratesmentioning
confidence: 99%
“… (E) Photophoretic levitation of a mylar film from the substrate. Figures reproduced from: (A and B) ( Lu et al, 2017b ) Copyright 2017, American Physical Society; (D and E) ( Azadi et al, 2021 ) Copyright 2021, American Association for the Advancement of Science. …”
Section: Optical Techniques For Manipulation On Solid Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that ultralight aerogels with density less than air density can be levitated in air by controlling the temperature and selectively expanding the air inside the aerogel [ 22 ]. Such ultralight materials with ultimate lightness have the potential for further applications such as in communication and sky transportation [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we levitated mock payloads heavier than the plates themselves (silicon pieces with milligram-scale mass). Silicon-based "smart-dust" systems with similar mass have been demonstrated to have extensive sensing, communications, and power capabilities [4,5].…”
mentioning
confidence: 99%